Adaptive Urban Renewal Concept Application at Pasar Lama Tangerang, Banten, Indonesia - Chandra, Jennifer Angelyn; Olivia, Deasy; Hardi, Rachmat Taufick (Department of Architecture, Faculty of Engineering, Universitas Diponegoro, Indonesia., 2024)
City will always shift and be dynamic. Pasar Lama of Tangerang is the point-zero of Tangerang development as a city, mainly influenced by the Chinese immigrants that move from China and sail to Tangerang. This made Pasar Lama valuable in terms of cultural richness and economic development. But, in times of modern era, Pasar Lama has shifted. The case of Pasar Lama shows how identity shift of a place could result in development imbalance, even harm the cultural product that has developed for hundreds of years. The disruption is caused by the regulation by government and the tourism activities in Pasar Lama that disregards the importance of cultural heritage. This research aims to see the application of adaptive urban renewal approach for cultural heritage space. This research is based on fragmental approach, with descriptive qualitative and spatial analysis. The result shows that adaptive urban renewal application is done through street space optimization to help support tourism, creating pedestrian-only alley that highlights the cultural heritage buildings, and creating a neutral space to bridge two different big cultures. To summarize, adaptive urban renewal could be implemented in Pasar Lama in terms of creating timeless space, which will encourage cultural activities and awareness; all the while maintaining culinary tourism.